Digital engagement in pronunciation learning: effects on learning performance and language anxiety - Fei, Ping Por (2020)
The aim of this study was to investigate the effects of digital engagement towards the pronunciation performance of high, medium and low anxiety learners. The ePronounceTM was designed and developed in this study to enable the learners to engage with three presentation modes: Text+Sound+Phonetic Symbols(TSP), Text+Sound+Phonetic Symbols+Mouth Movements(TSPM), and Text+Sound+Phonetic Symbols+Face Gestures(TSPF). The Foreign Language Classroom Anxiety Scales (FLCAS) was employed to measure different levels of language anxiety, and the Pronunciation Competence Test was used as pretest and posttest to evaluate the pronunciation performance. The sample consisted of 329 Primary Five students from three different schools in Malaysia. Analyses of covariance (ANCOVA) and pairwise comparisons were conducted to examine the main effects and the interaction effects. The findings showed that there was no significant difference in the achievement scores attained by learners with different levels of language anxiety in the three presentation modes. Seemingly digital engagement is able to bring the low and high language anxiety students to medium language anxiety level for optimal learning under optimal learning condition as explained in the curvilinear relationship between anxiety and performance.